The effect of different surface treatments on roughnessand bond strength in low fusing ceramics - KARA, ÖZLEM; Kara, Haluk Baris; Ozturk, A. Nilgun; Aykent, Filiz; Koc, Ozlem; Ozturk, Bora (My University, 2011)
The aim of this study was to evaluate the influence of different surface treatments (air abrasion, acid etching, and laser irradiation) on the surface roughness and bond strength of a low fusing ceramic. Thirty-six discs of low fusing ceramic (Finesse, Ceramco) were prepared (10 mm in diameter and 2 mm in thickness) according to the manufacturer-s instructions. Specimens were divided into three groups (n = 12), and the following treatments were performed: Air abrasion with alumina particles (50 mu m), acid etching with 5% HF and Nd:YAG laser irradiation (distance: 1 mm, 100 mJ, 20 Hz, 2 W, and 141.54 J/cm(2)). Following determination of surface roughness (R-a) by profilometry, specimens were examined with scanning electron microscopy (SEM). The luting cement (Clearfil Esthetic Cement) was bonded to the ceramic specimens using Teflon tubes. After 24 h of water storage, shear bond strength test was performed using a universal testing machine at a crosshead speed of 1 mm/min. The data were analyzed with two-way analysis of variance (ANOVA) and Tukey HSD tests (alpha = .05). Two-way ANOVA indicated that surface roughness was significantly affected by surface treatments (p .05). The SEM image of the laser irradiation surface appeared to be relatively smooth as compared to the images of other the groups. Air abrasion of low-fusing porcelain surfaces was effective in improving the bond strength as compared to the acid-etching and laser-irradiation methods.